2016
DOI: 10.1016/j.electacta.2016.01.200
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Composition and Activity of Cobalt Titanium Oxide Catalysts for the Oxygen Evolution Reaction

Abstract: Understanding catalyst function to improve activity for the oxygen evolution reaction (OER) is key to increasing the overall efficiency of electrochemical water splitting, a promising method for sustainable and clean production of hydrogen. Using a straightforward and scalable sol-gel synthesis, we explore the effects of metal composition in Co x Ti 1-x O y on electrochemical activity, atomic structure, and electronic state. Physical and electronic characterization reveal that increased amounts of Ti stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Over the past few decades, separated non-noble metal catalysts that are optimized for HER and OER have emerged as novel materials for catalyzing water splitting, such as transition-metal nitrides, , carbides, , and sulfides for HER, perovskite oxides, , transition-metal oxides, , and hydroxides , for OER, which are quite prospective for replacing precious metal catalysts in large-scale applications. However, developing efficient and durable bifunctional electrocatalysts toward both HER and OER in the same electrolyte with advantages in terms of not only simplifying the system and reducing costs but also providing high efficiency is quite a challenge. …”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, separated non-noble metal catalysts that are optimized for HER and OER have emerged as novel materials for catalyzing water splitting, such as transition-metal nitrides, , carbides, , and sulfides for HER, perovskite oxides, , transition-metal oxides, , and hydroxides , for OER, which are quite prospective for replacing precious metal catalysts in large-scale applications. However, developing efficient and durable bifunctional electrocatalysts toward both HER and OER in the same electrolyte with advantages in terms of not only simplifying the system and reducing costs but also providing high efficiency is quite a challenge. …”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential of ALD to allow the conformal deposition of nanoscale thin-film catalysts on large-surface-area electrodes, little research has been reported on CoO x using ALD for electrochemical water splitting. In addition, while many studies on the catalytic activity of CoO x use simple planar electrodes such as glassy carbon , and fluorine-doped tin oxide (FTO), , we used ALD to directly grow nanoscale CoO x films on self-supporting carbon fiber paper electrodes. Taking advantage of the excellent step coverage of the ALD process, we were able to prepare carbon fiber paper composed of complex 3D-structured carbon fibers decorated by the uniform nanoscale CoO x thin-film electrocatalyst (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Doping TiO 2 to increase its OER activity is also a well-established technique. [28][29][30][31][32][33] This work demonstrates the activation of TiO 2 for OER catalysis by subsituting Ti-atoms with both n-and p-type dopants. [34][35][36] Such co-substitution has never beento the best of our knowledgeapplied in electrocatalysis.…”
Section: Introductionmentioning
confidence: 74%